Proposals for consideration at IMC12 to modify provisions related solely to fungi in Chapter F of the International Code of Nomenclature for algae, fungi, and plants - Tom W. May; David L. Hawksworth (IMA Fungus)
Abstract Seven proposals or sets of proposals to modify the provisions of Chapter F of the International Code of Nomenclature for algae, fungi, and plants (ICNafp) have been received. These proposals are formally presented together here. The topics addressed relate to: fungi whose morph-names have the same epithet; the listing of synonyms under entries for protected names in the Code Appendices; the processes of protection and rejection; the use of DNA sequences as nomenclatural types; the use of genomes as nomenclatural types; and the designation of fungi known only from DNA sequences. In addition, a suggestion is included to update the mention of the World Directory of Culture Collections in Article 40.7 Note 4. A Synopsis of the formal proposals will be provided in early July 2024, and the mycological community will be invited to provide a guiding vote on the proposals with a closing date of 2 August 2024. Final decisions on the proposals will be made following debate at the Fungal Nomenclature Session of IMC12 in August 2024.